Identification of novel 1, 2, 3, 6-tetrahydropyridyl-substituted benzo[d]thiazoles: Lead generation and optimization toward potent and orally active EP1 receptor antagonists. Issue 13 (1st July 2017) - Umei, Kentaro; Nishigaya, Yosuke; Tatani, Kazuya; Kohno, Yasushi; Tanaka, Nobuyuki; Seto, Shigeki
Graphical abstract: Abstract: Herein we described the design, synthesis and evaluation of a novel series of benzo[ d ]thiazole derivatives toward an orally active EP1 antagonist. Lead generation studies provided benzo[ d ]thiazole core from the four designed scaffolds. Optimization of this scaffold in terms of EP1 antagonist potency and ligand-lipophilicity efficiency (LLE; pIC50 -clogP) led to a 1, 2, 3, 6-tetrahydropyridyl-substituted benzo[ d ]thiazole derivative, 7r (IC50 1.1 nM; LLE 4.7), which showed a good pharmacological effect when administered intraduodenally in a 17-phenyl trinor-PGE2 (17-PTP)-induced overactive bladder model in rats.